VIDEO AND IMAGE ACQUISITION CHALLENGES TO DEFINE IMAGE RESOLUTIONS FOR HEVC - Swamy T N,Ramesha K (International Journal of Advanced Science and Technology, 2020)
Video Acquisition and Image Acquisition plays an important role in defining different resolutions and provides different levels of details to map precise features with respect to exact scale of mapping. The different types of images are considered for image resolution analysis for High Efficiency Video Coding (HEVC) encoders. Graphic Interchange Format (GIF), Joint Photographic Experts Group (JPEG), Portable Network Graphics (PNG) images are scaled up with various factors and different levels of details are identified and quality of different resolutions is analyzed with Peak Signal to Noise Ratio (PSNR) and Mean Square Error (MSE).